The 3 power values : how commitment, integrity, and transparency clear the roadblocks to performance - Gebler, David, 1959- (San Francisco, CA : Jossey-Bass, 2012)
'Get organizational results by nurturing commitment, integrity, and transparency. A healthy corporate culture is the secret to an organization's performance. The good news is that employees already embody the values needed to propel the organization to its goals, but institutional roadblocks get in the way. All too often leaders don't know how to diagnose their culture in order to clear these roadblocks to performance. The 3 Power Values presents a breakthrough model that permits leaders to measure and manage culture. To create a fully aligned high-performing culture, leaders need only focus on nurturing three catalyst values: Commitment, Integrity, and Transparency. Offers an innovative values-centered model to help organizations achieve short-term goals without sacrificing long-run sustainability Filled with lively case studies of major companies including Johnson & Johnson and Boeing David Gebler is a recognized thought leader in the field of values-based ethics and culture risk management The 3 Power Values offers leaders at all levels a unique and accessible approach to identifying the behavioral challenges that are hindering their corporate culture and to removing them effectively'--
Includes bibliographical references and index.
Keywords: Commitment (Psychology).; Integrity; Corporate culture; Organization; BUSINESS & ECONOMICS / Management